Is there evidence of selection in the dopamine receptor D4 gene in Australian invasive starling populations?. Issue 3 (1st June 2015) - Rollins, Lee Ann; Whitehead, Michael R.; Woolnough, Andrew P.; Sinclair, Ron; Sherwin, William B.
Abstract: Although population genetic theory is largely based on the premise that loci under study are selectively neutral, it has been acknowledged that the study of DNA sequence data under the influence of selection can be useful. In some circumstances, these loci show increased population differentiation and gene diversity. Highly polymorphic loci may be especially useful when studying populations having low levels of diversity overall, such as is often the case with threatened or newly established invasive populations. Using common starlings Sturnus vulgaris sampled from invasive Australian populations, we investigated sequence data of the dopamine receptor D4 gene ( DRD4 ), a locus suspected to be under selection for novelty-seeking behaviour in a range of taxa including humans and passerine birds. We hypothesised that such behaviour may be advantageous when species encounter novel environments, such as during invasion. In addition to analyses to detect the presence of selection, we also estimated population differentiation and gene diversity using DRD4 data and compared these estimates to those from microsatellite and mitochondrial DNA sequence data, using the same individuals. We found little evidence for selection on DRD4 in starlings. However, we did find elevated levels of within-population gene diversity when compared to microsatellites and mitochondrial DNA sequence, as well as a greater degree of population differentiation. We suggest that sequence data from putatively nonneutral loci are a useful addition to studies of invasive populations, where low genetic variability is expected.